(untitled) (Revista LIDER, 2020)
This article presents an approximation to the phenomena of social exclusion from the disciplinary paradigms of literatura, psychiatry and the social scienes en the comuna of Osorno. We analyze the hypothesis that suggests that exclusion from the affiliation networks would be a discourse with which the society of Osorno identifies. Poetic texts are analyzed where social exclusion is evidenced through crazyness and displacement toward urbanity; official sources are studied that provide statistics in relation to suicide in Chile and in the city of Osorno. Given the epidemiological evidence of overmortailty of the indigenous population in the country and the region, this could only be explained as a result of social determinants. The considerations on social exclusion are intended to show an integrated view of phenomena that are not only explained from individual subjectivity, but also from the social and territorial dimensions.